2021
DOI: 10.1002/ps.6431
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ATP‐binding cassette transporters associated with sulfoxaflor resistance in Aphis gossypii glover

Abstract: BACKGROUND Sulfoxaflor is a new insecticide for controlling against Aphis gossypii in the field. ATP‐binding cassette (ABC) transporters belong to a large superfamily of proteins and play an important role in the detoxification process. However, the potential role of ABC transporters in sulfoxaflor resistance in A. gossypii is unknown. RESULTS In this study, an ABC transporter inhibitor, verapamil, dramatically increased the toxicity of sulfoxaflor in the resistant population with a synergistic ratio of 8.55. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…35 Mastrantonio et al 24 found that, in Anopheles gambiae third-instar larvae, permethrin combined with verapamil treatment increased the knockdown rate 15-fold more than that of permethrin treatment alone. Wang et al 36 reported that an artificial diet with verapamil significantly increased the toxicity of sulfoxaflor by 8.55-fold in Aphis gossypii glover Sul-R population. These results were in accordance with those observed in our study because verapamil oral treatment followed by deltamethrin treatment increased mosquito knockdown rate in wildtype populations.…”
Section: Discussionmentioning
confidence: 99%
“…35 Mastrantonio et al 24 found that, in Anopheles gambiae third-instar larvae, permethrin combined with verapamil treatment increased the knockdown rate 15-fold more than that of permethrin treatment alone. Wang et al 36 reported that an artificial diet with verapamil significantly increased the toxicity of sulfoxaflor by 8.55-fold in Aphis gossypii glover Sul-R population. These results were in accordance with those observed in our study because verapamil oral treatment followed by deltamethrin treatment increased mosquito knockdown rate in wildtype populations.…”
Section: Discussionmentioning
confidence: 99%
“…The midgut is the first line of defense after the ingestion of toxic substances by insects, and it is one of the most vital detoxifying organs for larvae . Furthermore, the increased level of ABC transporter gene transcription is generally considered to be a common molecular mechanism by which insect pests defend against insecticides. , Fluorescence imaging showed that Texas Red appeared in the midgut tissue at 24 h post-injection (no fluorescence signal was observed in the midgut tissue at 0 h), indicating that part of the Texas Red injected into aphids was transported to the midgut tissue. Both the Texas Red fluorescence intensity of the whole body and midgut showed almost no fluorescence at 72 h post-injection, suggesting that the Texas Red transported to the midgut tissue was finally excreted out of the body (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Detoxifying enzymes contribute considerably to the development of insecticide resistance in aphids. For example, the peach potato aphid Myzus persicae is able to generate resistance to sulfoxaflor via overexpression of many detoxification-related enzymes, including UDP-glucuronosyltransferase (UGT) and cytochrome P450 (CYP) enzymes 14 , and Aphis gossypii overcomes sulfoxaflor through the up-regulation of ATP-binding cassette (ABC) transporter expression 15 . One practical and sustainable strategy to reduce insecticide applications is the cultivation of aphid-resistant plants 16 .…”
Section: Background and Summarymentioning
confidence: 99%